(untitled) (Bangladesh Journal of Botany, 2020)
In vitro micropropagation was studied in two species of Ocimum and one species was used for antioxidant and antibacterial activity. The maximum number of shoots/explant (10.1 and 9.5) was induced in MS + 1.0 mg/l BAP + 0.5 mg/l Kn and MS + 2.0 mg/l BAP + 0.5 mg/l IAA in Ocimum tenuiflorum and O. americanum, respectively. GA3 (0.1 mg/l) was found to be effective for shoot induction and elongation in both the species. Strong and stout root formation was observed on half strength MS medium supplemented with 0.2 mg/l IBA for O. tenuiflorum and half strength MS + 0.5 mg/l NAA for O. americanum. Methanolic leaf extract of O. tenuiflorum showed high inhibition of DPPH activity compared to standard antioxidants like quercetin and the chloroform leaf extracts exhibited wide range of antibacterial activity.